Surviving suicide loss: recommendations for research - Neimeyer, Robert; Cerel, Julie (Acta Universitaria, 2015)
Mounting scientific evidence documents that bereavement by suicide can have a powerful and sometimes devastating impact on survivors. Accordingly, the Survivors of Suicide Loss Task Force of the National Action Alliance for Suicide Prevention in the United States has recently worked to formulate national guidelines to mitigate the harmful after-effects of suicide in social and family systems. The present article addresses one of four strategic directions addressed by the Task Force, namely the development of goals and objectives for surveillance, research and evaluation of the impact of suicide loss. Recommendations range from methodological guidelines for the conduct of future studies to specific content areas of research relevant to the design and implementation of public health, peer support and professional psychotherapeutic attention for communities, families and individuals affected by suicide loss.
Keywords: Array; Array; Array; Array